Abordagem de temáticas da ditadura civil-militar no Jornal “Gazeta de Sergipe” (1968 – 1978) - Barreto, Mayra Ferreira (2020)
The research presents reflections regarding the use of Sergipe newspapers as a source for the teaching of history in the final years of elementary school, valuing them as a didactic potential for historical learning, especially in the approach of themes and / or objects of knowledge (BNCC, 2019), related to the period of the Civil-Military Dictatorship in Brazil. The chosen journal was Gazeta de Sergipe, a newspaper that had a large circulation in the capital during the period studied, in addition to being digitalized and made available by the Library System of the Federal University of Sergipe (Sibiufs), accessible at the following address: newspapersdesergipe.ufs.br/. The work aims to: discuss issues related to the use of Sergipe journalistic sources as a didactic resource in the teaching of History; contribute to the valorization of local historical issues related to the national theme; and understand how the Gazeta de Sergipe portrayed the Civil-Military Dictatorship for society in Sergipe. The research dialogues with studies in the field of historical education, in particular, with the studies of Rüsen (2006); Isabel Barca (2001, 2004, 2006); Peter Lee (2006); Schmidt (2009); Germinari (2011); Barbosa (2007). As a methodological proposal, the research is divided into the following stages: analysis of all editions of Gazeta de Sergipe between the years 1968 and 1978, cataloging the selected articles and dividing them into four thematic axes: “Propagating the ideas of the '1964 Revolution' to the people of Sergipe”; “Resistances to the Dictatorship”; "The Institutional Acts of the Military Regime" and "In the name of Economic Development”. The final product of the research is the production of an activity notebook, with proposals and scripts to be explored and used by students with the help of the teacher. The product will allow the history teacher to discuss critically with students representations about the Civil-Military Dictatorship in Brazil and its relations with the present, as well as that they understand aspects of the production of historiographic knowledge and observe in practice the use of the method investigative history.